Fertigation of blueberries grown in pots: An example of the case of blueberry fertigation in Nemenikuca - Savić Srđan; Antić-Mladenović Svetlana; Pavlović Miloš; Stojanović Miloš; Marjanović Uroš; Stričević Ružica (Zemljište i biljka, 2024)
The aim of this research is to present the technology of blueberry cultivation, especially from the aspect of fertilization and irrigation (fertigation), and the water use efficiency obtained in blueberry plantations grown in pots. In order to obtain optimal yields, irrigation and nutrition of the plants must be well coordinated, which is shown in this work. The experiment was located in Nemenikuća, Sopot municipality. The location is suitable for blueberry cultivation due to topography, altitude, climatic factors and water supply. Blueberries were planted in 45-liter pots, which was sufficient to obtain high yields. The substrate used was "Legro" with 25% perlite. Dripper with a flow rate of 4 L and a divided sub-dropper for uniform distribution of water in the pot was used. The irrigation system was also equipped with devices that extract the appropriate amount of fertilizer from the tank over the set of pH and EC values. This way of water distribution enables precise control of the quality and parameters of the irrigation water, such as pH and electrical conductivity (EC). Good drainage of the pot is ensured by perforations of the bottom and sides of the pot with several openings of different sizes and shapes. It is desirable that the bottom of the pot is separated from the substrate. The amount of water used for vegetation was 2,817,700 L or 2817.7 m3 of water for 9,000 plants. A yield of 14,000 kg of blueberries was obtained in second year and 38.000 kg in the third growing year. This means that 201.21 L of water was used for the yield of 1 kg of blueberries or 4.96 kg of blueberry can be produced using 1 m3 of water. Most of the water was applied in July (92 L per pot). The EC of the solution was variable from day to day, depending on the amount of nutrients consumed by blueberry. Water consumption was determined partly by the duration of irrigation and by the amount of drained water. The pH and EC values of the water were measured daily. The pH in the irrigation water was maintained in the range of 5.0-5.5 and the ES of 1.3-2.5 dS/m, in the drainage water 0.6 to 2.3 dS/m. In the year of replanting 77 g of yield per plant wwas obtained. Very high yields, as high as 1.5 kg per plant were obtained in the first year of production and as high as 4.2 kg per plant in the second year of production. The average water consumption during the growing season was 3 L per plant, and total water consumption during first yielding year was 313 L.